Enhancing Photoirradiation Stability: A Review on Modification of Poly(methyl methacrylate) - Adil, Hadeel; A. Ibraheem, Hanan; Ghazi Naser, Huda; R. Shaker, Ala’a; Salman, Husam; Al-Mashhadani, Mohammed; Abdullayeva, Maya; Fellah, Mamoun; A. Husain, Amani; Yousif, Emad (Al-Nahrain Journal of Science, 2024)
Due to photoirradiation-induced deterioration, poly(methyl methacrylate) (PMMA), a thermoplastic that is extensively used and valued for its transparency and adaptability, performs less well in a variety of applications. This extensive analysis looks at creative approaches to improve the photoirradiation stability of PMMA, mostly concentrating on pendant modification techniques. The first sections of the paper explain the importance of stability in PMMA, describe the difficulties caused by photoirradiation, and state the goals of the review. An in-depth analysis of PMMA, including its attributes, traits, and many uses, prepares the reader for the investigation of stability improvement methods that follow. The literature review section explores previous research on PMMA stability, pointing out knowledge gaps and areas needing more research. After that, the focus turns to pendant customization and offers a thorough explanation, illustrations, and change procedures. An extensive analysis is conducted on many pendant modification methods, such as photostabilizing nanoparticles, hindered amine light stabilizers, and grafting of benzotriazole derivatives. Comparative evaluations draw attention to the advantages and disadvantages of each method. Optical devices, automotive components, and architectural glazing are identified as domains in which modified PMMA exhibits exceptional performance.